Evaluación de la calidad de suelo en las microcuencas (Hualcanga y Jatuchimbana), del páramo cerro Igualata, provincia de Tungurahua - Mueses Ortega, María José; Quishpi Tene, Mélody Tamara (2025)
The purpose of this research was to evaluate soil quality in the Hualcanga and Jatuchimbana microbasins of the Igualata páramo, using physical, chemical, and biological parameters. The research was quantitative and qualitative, based on sampling in three transects (páramo, pasture, and crop), from each of which five soil samples were taken. The results showed soil color, according to the Munsell system, with predominant shades of 10YR and 7.5YR, and texture varied between sandy loam and sandy loam. In Hualcanga, high Dap values were observed, associated with land-use change; in contrast, Jatuchimbana presented low Dap values, suggesting greater soil structural stability. Regarding pH, the soils were acidic, and organic carbon was higher in the páramo, decreasing in disturbed soils. SCI values reflected a reduction in soils transformed from páramo to pasture or crop. These findings show that human activities affect the quality of the páramo soil, especially its carbon content, the loss of which causes CO2 emissions. In conclusion, the Jatuchimbana microbasin has better soil conditions due to its lower level of disturbance.